Duplex solid solution treatment process of 68NiCrWCoTiAl alloy

Through the dual solution treatment process, air-cooling treatment was performed first at 1160℃×1h after insulation to reduce internal stress; then water-cooling treatment was performed after insulation to reduce internal stress and improve plasticity, which solved the solution of 68NiCrWCoTiAl alloy in solid solution The internal cracks and final performance failure problems during treatment have achieved a 100% pass rate of solution treatment and a high-quality yield rate.

CN119433395AActive Publication Date: 2025-02-14CHONGQING MATERIALS RES INST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411625001.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

68NiCrWCoTiAl alloy is prone to internal cracks and final performance problems during solid solution treatment, resulting in high product scrapping rate and low yield rate.

Method used

The dual solution treatment process is adopted, and air-cooling treatment is performed after insulation at 1160℃×1h to reduce the internal stress during the cooling process; then water-cooling treatment is performed after insulation at 1080℃×1h to reduce the internal stress and improve plasticity.

Benefits of technology

It effectively avoids the occurrence of internal cracks, stabilizes the final performance requirements, improves the pass rate of solid solution treatment to 100%, and ensures the quality of finished products and yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a duplex solid solution treatment process of 68NiCrWCoTiAl alloy, which adopts the duplex solid solution treatment process of cold charging, heat preservation at 1160 DEG C for 1 hour, air cooling, cold charging again, heat preservation at 1080 DEG C for 1 hour and water cooling, can avoid the generation of internal cracks during solid solution treatment in the production process of 68NiCrWCoTiAl alloy material with high crack tendency and difficult to process, and stably meets the final performance requirements. And the qualified rate of solution treatment reaches 100%, the finished product quality is stable, potential quality hazards and risks do not exist, the method has the advantages of being high in feasibility, reliability and yield and good in quality, and a solution is provided for normal manufacturing of the alloy material. The process disclosed by the invention can be suitable for batch production of products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heat treatment of special alloys, and relates to a double solid solution treatment process for preventing internal cracks from being generated during solid solution treatment of a high crack tendency difficult to process 68NiCrWCoTiAl alloy in the production process, and stably achieving final performance requirements. Background Art

[0002] Special alloys mainly include high-temperature alloys, corrosion-resistant alloys, metal functional materials, special stainless steels, etc. Special alloy materials usually include bars, strips, wires, plates, strips, tubes, etc., with various specifications and sizes. Among them, bars, strips and other products usually need to be solution treated before cold drawing or when they are finished, in order to soften the performance of the alloy billet or finished product.

[0003] However, there are some problems in the solution treatment of a small amount of special grades in special alloys (especially high-temperature alloys). Among them, the 68NiCrWCoTiAl alloy is prone to internal cracks and unqualified final performance during solution treatment, resulting in product scrapping and low yield. For 68NiCrWCoTiAl alloy, there are two solid solution treatment processes currently used, both of which are single-link solid solution treatment processes. Either the single-link solid solution treatment process of "cold charging furnace, 1160℃×1h insulation, water cooling" (A process) is used, which is characterized by a high final performance qualified rate, but the proportion of internal cracks is as high as about 30%, and the scrap rate due to internal cracks is high, resulting in a high total scrap rate; or the single-link solid solution treatment process of "cold charging furnace, 1080℃×1h insulation, water cooling" (B process) is used, which is characterized by a reduced proportion of internal cracks, only about 15%, and a reduced scrap rate due to internal cracks, but the yield strength is reduced, the plasticity is reduced, and the final performance is easy to get stuck. The qualified rate is reduced due to the final performance, resulting in no significant change in the total scrap rate, which is still high. When using these two single-link solid solution treatment processes, although each can be successful, either the internal crack problem is mainly generated, or the final performance is unqualified, both of which will cause product scrapping and low finished product rate.

[0004] It can be seen that after the solution treatment of 68NiCrWCoTiAl alloy, the first problem is the generation of internal cracks. The cracks are almost all transverse cracks, with a proportion of 15-30%, which seriously affects the product yield and has serious quality risks; the second is the problem of final performance qualification rate, which also affects the product yield; the influence of both together causes the product yield to be significantly low. The reason is that in 68NiCrWCoTiAl alloy, the content of alloying elements such as carbon, tungsten, molybdenum, cobalt, titanium and aluminum is very high, so it has the significant characteristics of high crack tendency and difficult processing. Conventional processes are prone to low alloy yield, and the quality of its finished products is also prone to serious uncertainty and other problems, becoming a technical obstacle to the production of alloy materials. Researching new solution treatment processes, while solving problems such as easy internal cracks and unqualified final performance, and fundamentally improving the yield are issues of great concern to technicians in this field. Summary of the invention

[0005] The present invention provides a double solid solution treatment process for a 68NiCrWCoTiAl alloy that is difficult to process and has a high crack tendency. The double solid solution treatment process of "cold charging furnace, first 1160℃×1h insulation, air cooling, then cold charging furnace, 1080℃×1h insulation, water cooling" is adopted. Internal cracks will not be generated, and the final performance requirements can be stably achieved. The qualified rate of solid solution treatment is increased to 100%. The process of the present invention is suitable for the solid solution treatment of 68NiCrWCoTiAl alloy, and has the advantages of good feasibility, reliability, high yield rate and high quality.

[0006] The technical solution of the present invention is: The duplex solid solution treatment process of 68NiCrWCoTiAl alloy includes the following steps: 1) First joint solution treatment S1, loading the material to be treated into the heat treatment furnace at a temperature of ≤100°C; the loading position is within the effective working area of ​​the heat treatment furnace; S2, raise the temperature of the heat treatment furnace to the holding temperature of 1160±5℃ and keep it for 1h; S3, taking the material to be treated out of the furnace and cooling it naturally in the air to room temperature ~ 100°C; 2) Second solution treatment S4, loading the material to be treated after the first solid solution treatment into a heat treatment furnace at a temperature of ≤100°C; the loading position is within the effective working area of ​​the heat treatment furnace; S5, raising the temperature of the heat treatment furnace to a holding temperature of 1080±5°C and keeping it at that temperature for 1h; S6, take the material to be processed out of the furnace and quickly put it into water for water cooling within ≤90 seconds.

[0007] The heat treatment furnace in steps S1 and S4 is an electrically heated heat treatment furnace.

[0008] The effective working area described in steps S1 and S4 is a uniform temperature area.

[0009] The temperature of the heat treatment furnace described in steps S1 and S4 should be tested for furnace temperature uniformity, and the furnace temperature deviation and furnace temperature uniformity should meet the requirements of ±10°C.

[0010] In the furnace loading described in steps S1 and S4, a shim with a height of 30 to 50 mm should be placed under the material to be processed.

[0011] The heating rate of the heat treatment furnace from step S2 to step S5 to the holding temperature is 280±30°C / h.

[0012] The rapid water cooling in step S6 is that the time from leaving the furnace to entering the water is ≤ 90 seconds, and the cooling water should be kept flowing.

[0013] The temperature of the cooling water during the rapid water cooling in step S6 is ≤30°C, and the temperature of the cooling water after the material to be treated is cooled after entering the water should be ≤35°C.

[0014] The mass percentage of each component of the chemical composition of the 68NiCrWCoTiAl alloy described in the present invention is C≤0.05%, Si≤0.4%, Mn≤0.4%, S≤0.010%, P≤0.015%, Cr 18-20%, Ti 2.7-3.2%, Al 1.3-1.8%, Co5.5-6.7%, W 9.0-10.5%, Ce≤0.05%, B≤0.003%, Nb≤0.2%, V≤0.2%, Cu≤0.07%, Fe≤1.0%, and Ni balance.

[0015] In the process described in the present invention, the holding temperature, holding time and cooling method of the first solid solution treatment are "1160℃×1h holding, air cooling". The cooling method is changed from water cooling to air cooling. Because the cooling process is slow, the internal stress generated by the internal and external temperature difference during the cooling process of the first solid solution treatment is reduced, and the cracks caused by excessive internal stress are eliminated; but because the cooling rate during the air cooling process is slow, it cannot quickly cross the 650-820℃ aging temperature range of the alloy, and a partial aging effect will be produced when it is in this aging temperature range during the cooling process. In addition, the slow cooling process will produce more curved grain boundaries, all of which lead to a significant increase in strength (qualified) and a significant decrease in plasticity (unqualified). Through the first solid solution treatment, the primary internal crack problem is eliminated. Although the performance is not fully qualified at this time, high strength and low plasticity are relatively easy to solve. This lays a good foundation for the final performance to be qualified by using the second solid solution treatment to slightly reduce the strength and significantly improve the plasticity to correct the performance.

[0016] The holding temperature, holding time and cooling method of the second solid solution treatment are "1080℃×1h holding, water cooling". The second solid solution treatment can withstand greater internal stress based on the higher strength after the first solid solution treatment; the holding temperature of the second solid solution treatment is 1080℃, which is lower than the holding temperature of 1160℃ which is easy to produce internal cracks. The internal stress generated by the temperature difference between the inside and the outside during the cooling process is reduced, so that the alloy will not produce internal cracks under the combined effect of high strength and reduced internal stress. At the same time, through the second solid solution treatment, due to the low holding temperature, the effect of reducing the high strength formed after the first solid solution treatment is small; because the cooling method is water cooling, the effect of improving the low plasticity formed after the first solid solution treatment is obvious; in this way, based on the good performance established during the first solid solution treatment, the final performance after the second solid solution treatment is easily qualified, and there are no internal cracks.

[0017] The process of the present invention does not simply combine two single solution treatment processes together, but changes the cooling mode of the first solution treatment to air cooling, keeps the cooling mode of the second solution treatment to water cooling, and then combines the two processes, comprehensively utilizing the beneficial effects of each solution treatment on the alloy material, matching the two processes, and achieving the best solution treatment effect. It will not produce internal cracks and stably achieve the final performance requirements (mainly mechanical properties, such as tensile properties, impact properties, hardness, etc.). The qualified rate of solution treatment is increased to 100%, solving the problems of the previous two single solution treatment processes that are prone to internal cracks and unqualified final performance.

[0018] The main features of the process of the present invention are compared with those of the previous solution treatment process, as shown in Table 1.

[0019] Table 1 Comparison of the main features of the process described in the present invention and the previous solution treatment process Beneficial effects of the present invention

[0020] Therefore, the use of a double solution treatment process instead of the previous two single solution treatment processes in the present invention can avoid the problem of internal cracks generated during solution treatment in the production process of the difficult-to-process 68NiCrWCoTiAl alloy material with high crack tendency, and stably achieve the final performance requirements. The qualified rate of solution treatment reaches 100%, eliminating the serious uncertainty of finished product quality and serious quality hidden risks. The yield and quality are both guaranteed with certainty, providing a perfect solution for the normal manufacturing of the alloy material, and has the advantages of feasibility, high reliability, high yield and good quality.

[0021] The process of the present invention is suitable for mass production of products.

[0022] The applicant's implementation shows that, by using the process of the present invention, the 68NiCrWCoTiAl alloy material has no internal cracks and the quality pass rate is 100%; the tensile strength of the alloy bar is 1360.4-1369.4MPa, the yield strength is 876.9-898.4MPa, the elongation is 23-23.5%, the cross-sectional shrinkage is 27-29%, and the impact toughness (U-notch) is 45-50 J / cm 2 , Brinell hardness HBW10 / 3000 is 345~362, which meets the requirements, and the final performance qualification rate is 100%; the comprehensive qualification rate is 100%, which can fully meet the needs of scientific research and production, and the effect is very good. DETAILED DESCRIPTION

[0023] The heat treatment furnace of the process of the present invention adopts an electrically heated heat treatment furnace, and the specific steps are as follows: 1) First joint solution treatment S1, load the material to be treated into the heat treatment furnace when the temperature is ≤100℃; the loading position is within the effective working area (temperature-averaging area) of the heat treatment furnace; place a pad with a height of 30-50mm under the material to be treated to prevent the material to be treated from directly contacting or approaching the heating element of the bottom plate of the heat treatment furnace to cause local overheating; S2, raising the temperature of the heat treatment furnace to a holding temperature of 1160±5°C and keeping it for 1 hour; the heating rate is 280±30°C / h; S3, taking the material to be treated out of the furnace and cooling it naturally in the air to room temperature ~ 100°C; 2) Second solution treatment S4, loading the material to be treated after the first solid solution treatment into the heat treatment furnace at a temperature of ≤100°C; the loading position is within the effective working area (temperature-averaging area) of the heat treatment furnace; placing a pad iron with a height of 30 to 50 mm under the material to be treated to prevent the material to be treated from directly contacting or approaching the heating element of the bottom plate of the heat treatment furnace to cause local overheating; S5, raising the temperature of the heat treatment furnace to a holding temperature of 1080±5°C and keeping it at that temperature for 1 hour; the heating rate is 280±30°C / h; S6, take the material to be treated out of the furnace and quickly put it into water for water cooling within ≤90 seconds; the cooling water temperature is ≤30℃ when entering the water, and the cooling water temperature should be ≤35℃ after the material to be treated is cooled after entering the water; the cooling water should be kept flowing.

[0024] The temperature of the above heat treatment furnace should be tested for furnace temperature uniformity, and the furnace temperature deviation and furnace temperature uniformity should meet the requirements of ±10℃. Example 1

[0025] According to the process of the present invention, a 68NiCrWCoTiAl alloy bar with a diameter of φ30mm is subjected to solid solution treatment, and no internal cracks are generated in the alloy material, and the quality pass rate is 100%; the tensile strength of the alloy bar is 1369.4MPa, the yield strength is 876.9MPa, the elongation is 23.5%, the cross-sectional shrinkage is 29%, and the impact toughness (U-notch) is 45 J / cm 2 , the Brinell hardness HBW10 / 3000 is 345, which meets the requirements, and the final performance qualification rate is 100%; the comprehensive qualification rate is 100%, which fully meets the needs of scientific research and production, and the effect is very good. Example 2

[0026] According to the process of the present invention, a 68NiCrWCoTiAl alloy straight bar with a diameter of φ16 mm is subjected to solid solution treatment, and the alloy material has no internal cracks, and the quality pass rate is 100%; the tensile strength of the alloy straight bar is 1360.4MPa, the yield strength is 898.4MPa, the elongation is 23%, the cross-sectional shrinkage is 27%, and the impact toughness (U-notch) is 50 J / cm 2 , the Brinell hardness HBW10 / 3000 is 362, which meets the requirements, and the final performance qualification rate is 100%; the comprehensive qualification rate is 100%, which fully meets the needs of scientific research and production, and the effect is very good.

Claims

1. A duplex solid solution treatment process for 68NiCrWCoTiAl alloy, characterized in that: The following steps are involved: 1) First joint solution treatment S1, loading the material to be treated into the heat treatment furnace at a temperature of ≤100°C; the loading position is within the effective working area of ​​the heat treatment furnace; S2, raise the temperature of the heat treatment furnace to the holding temperature of 1160±5℃ and keep it for 1h; S3, taking the material to be treated out of the furnace and cooling it naturally in the air to room temperature ~ 100°C; 2) Second solution treatment S4, loading the material to be treated after the first solid solution treatment into a heat treatment furnace at a temperature of ≤100°C; the loading position is within the effective working area of ​​the heat treatment furnace; S5, raising the temperature of the heat treatment furnace to a holding temperature of 1080±5°C and keeping it at that temperature for 1h; S6, take the material to be processed out of the furnace and quickly put it into water for water cooling within ≤90 seconds.

2. The double solution treatment process according to claim 1, characterized in that: The heat treatment furnace in steps S1 and S4 is an electrically heated heat treatment furnace.

3. The double solution treatment process according to claim 1, characterized in that: The effective working area described in steps S1 and S4 is a uniform temperature area.

4. The double solution treatment process according to claim 1, characterized in that: The temperature of the heat treatment furnace described in steps S1 and S4 should be tested for furnace temperature uniformity, and the furnace temperature deviation and furnace temperature uniformity should meet the requirements of ±10°C.

5. The double solution treatment process according to claim 1, characterized in that: In the furnace loading described in steps S1 and S4, a shim with a height of 30 to 50 mm should be placed under the material to be processed.

6. The double solution treatment process according to claim 1, characterized in that: The heating rate of the heat treatment furnace from step S2 to step S5 to the holding temperature is 280±30°C / h.

7. The double solution treatment process according to claim 1, characterized in that: The rapid water cooling in step S6 is that the time from leaving the furnace to entering the water is ≤ 90 seconds, and the cooling water should be kept flowing.

8. The double solution treatment process according to claim 1, characterized in that: The temperature of the cooling water during the rapid water cooling in step S6 is ≤30°C, and the temperature of the cooling water after the material to be treated is cooled after entering the water should be ≤35°C.

Citation Information

Patent Citations

  • Heat treatment method for optimizing mechanical property of additive manufacturing GH3536 nickel-based superalloy

    CN113528992A

  • Surface treatment process for improving hydrogen embrittlement resistance of nickel-based corrosion-resistant alloy

    CN115679230A

  • Superalliage a base de nickel pour une piece de turbomachine

    FR3013060A1

  • TREATMENT METHOD FOR RESTORING PERFORMANCE OF Ni-BASED HEAT-RESISTANT ALLOY

    JP2005240186A

  • Method for producing ni-based super-heat-resistant alloy, and ni-based super-heat-resistant alloy

    WO2020195049A1